IMPLEMENTASI PKPU NOMOR 20 TAHUN 2018 STUDI KASUS DI KABUPATEN PANDEGLANG - Dede Qodrat Alwajir Dede Qodrat Alwajir; Irmayanti Irmayanti (NIAGARA Scientific Journal, 2021)
Various problems related to the implementation of the Implementation of the General Election Commission Regulation Number 20 Concerning the Nomination of the People's Legislative Council, the Provincial Regional People's Legislative Assembly and the Regency/City People's Representative Council in Pandeglang district such as the unclear size and objectives of the policy, disputes still occur between election organizers, namely the KPU and Bawaslu. In addition, the lack of help desk staff provided by the KPU hinders the implementation of regulations and the uneven distribution of human resources from political parties to understand the regulations that have been explained. The main problem of this research is: how is the Implementation of the Republic of Indonesia General Election Commission Regulation No. 20 of 2018 Case Study in Pandeglang Regency? The purpose of this research is to find out the implementation of these regulations in Pandeglang Regency. This study uses a type of qualitative research. This research was conducted at the General Election Commission of Pandeglang Regency. The data sources for this research were taken from primary and secondary data sources relating to the Implementation of General Election Commission Regulation Number 20. The results of the research show that the size and objectives of the policy are still fully agreed upon by the election organizers. The effectiveness of the help desk created by the KPU did not run optimally because it was only passive waiting for consultations from election participants. The characteristics of the implementing agency are quite good. The attitude of the tendency of the executor is quite good. Communication between organizations is quite good. The social and economic environment is quite good in supporting the implementation of the policy. Based on the research, it is known that four of the six indicators show positive results. So it can be concluded that the Implementation of the General Election Commission of the Republic of Indonesia Regulation No. 20 of 2018 in Pandeglang Regency was carried out well.